2.0 [compact disc] - Young, Brett, 1981- (Big Machine Label Group, 2025)
Brett Young's eighth studio album dives into his most personal and introspective storytelling yet, blending heartfelt lyrics with a fresh, dynamic sound. It reflects his growth as an artist, with songs that are more vulnerable and offer a deeper connection to his real-life experiences. The album features a mix of new tracks just written and older songs he's always believed needed to be heard. While Young's earlier music was about capturing the moment this album offers a glimpse into his evolving perspective.